Pengaruh Kredibilitas Endoser dan Daya Tarik Iklan terhadap Minat Beli Konsumen - Yudha, I Wayan Acarya; Risma M. Arsha, I Made (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This study aims to determine the partial and simultaneous effect of endorser credibility and advertising attractiveness on consumer buying interest in e-commerce Shopee in Badung Regency. The population in this study were all Shopee e-commerce consumers/users in Badung Regency. Determination of the sample using the Roscoe method as many as 120 respondents who were taken using the accidental sampling method. After carrying out the instrument test and classical assumption test, then data analysis was carried out using multiple linear regression analysis, determination, t test, and F test. The results of the analysis show that endorser credibility has a significant positive effect on consumer buying interest in e-commerce Shopee in Badung Regency . Advertising attractiveness has a significant positive effect on consumer buying interest in e-commerce Shopee in Badung Regency. Simultaneous endorser credibility and advertising attractiveness on consumer buying interest in Shopee e-commerce in Badung Regency.